2004
DOI: 10.1097/01.brs.0000102320.35490.43
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Functional Restoration Versus 3 Hours per Week Physical Therapy: A Randomized Controlled Study

Abstract: This study demonstrates the effectiveness of a functional restoration program on important outcome measures, such as sick leave, in a country that has a social system that protects people facing difficulties at work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
1
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(79 citation statements)
references
References 29 publications
1
73
1
4
Order By: Relevance
“…A more recent low quality RCT from the same research group (N=127), however, found that intensive multidisciplinary treatment and exercise therapy showed no significant differences in the resulting improvements in pain and function -only the global rating of "overall improvement" was better in the group of patients receiving the intensive treatment (Bendix et al 2000). An additional high quality trial (N=86) on patients with an average sick-leave of 6 months in the last 2 years found that the mean number of sick-leave days was significantly lower in the functional restoration group, but there was no significant difference in the intensity of pain, the quality of life, functional indexes, psychological characteristics, the number of contacts with the medical system, or the drug intake (Jousset et al 2004).…”
Section: Exercise (Outpatient) Versus Intensive Multidisciplinary Trementioning
confidence: 99%
“…A more recent low quality RCT from the same research group (N=127), however, found that intensive multidisciplinary treatment and exercise therapy showed no significant differences in the resulting improvements in pain and function -only the global rating of "overall improvement" was better in the group of patients receiving the intensive treatment (Bendix et al 2000). An additional high quality trial (N=86) on patients with an average sick-leave of 6 months in the last 2 years found that the mean number of sick-leave days was significantly lower in the functional restoration group, but there was no significant difference in the intensity of pain, the quality of life, functional indexes, psychological characteristics, the number of contacts with the medical system, or the drug intake (Jousset et al 2004).…”
Section: Exercise (Outpatient) Versus Intensive Multidisciplinary Trementioning
confidence: 99%
“…Developed in 1983, this rehabilitation program is a variant of chronic pain management based on the biopsychosocial model of pain and disability, and is specifically intended for rehabilitation of compensation injuries (Mayer et al, 1985). The efficacy of functional restoration for CDOMD, as well as the objective outcomes for treatment monitoring, have been extensively reviewed in the literature (Bendix et al, 1996;Hildebrandt, Pfingsten, Saur, & Jansen, 1997;Jousset et al, 2004;Mayer et al, 1998;Mayer et al, 1985;Mayer et al, 1987;Rainville, Kim, & Katz, 2007;Wright, Mayer, & Gatchel, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…Objective oneyear post-rehabilitation outcomes have been obtained from cohort studies, as well as RCTs, and include: increased resumption of active occupational status and activities of daily living; decreased health care utilization; reduced levels of pain intensity; improved readiness to change; improved psychological well being; and, resolution of outstanding medico-legal issues (Becker, Sjogren, Beck, Olsen, & Eriksen, 2000;Guzman et al, 2001;Hazard et al, 1989;Mayer et al, 1985;Patrick, Altmaier, & Found, 2004). The highly satisfactory results of functional restoration have been shown to be temporally stable (Mayer et al, 1987), and can be generalized across different socioeconomic and medico-legal systems (Bendix et al, 1996;Corey, Koepfler, Etlin, & Day, 1996;Hildebrandt, Pfingsten, Saur, & Jansen, 1997;Jousset et al, 2004). Finally, it has been demonstrated that functional restoration, along with other interdisciplinary approaches to pain management, are more cost-effective than standard conservative treatment (Gatchel & Okifuji, 2006;Skouen, Grasdal, Haldorsen, & Ursin, 2002;Turk, 2002;Turk & Okifuji, 1997).…”
Section: Tertiary Carementioning
confidence: 99%
See 1 more Smart Citation
“…Although many treatment modalities do promise relief of pain, not much evidence is present as to its true potential in relieving and curing the disability. With the question of immobilization during rehabilitation; many concluded the beneficial use of exercises (Hagen, 2000, Kuukkanen, 2000, Mannion, 2001, Moseley, 2002, Peterson, 2002, Aure, 2003, Liddle, 2004, Jousset, 2004, Niemisto, 2003. Interest then emerged in the role of manual therapy, mobilization and massage (Furlan, 2002, Hemmila, 2002, Aure, 2003, Cherkin, 2003, Chiradejnant, 2003, Harvey, 2003, Licciardone, 2003, Walach, 2003, Assendelft, 2004, Jette, 2006.…”
Section: Introductionmentioning
confidence: 99%